2020
DOI: 10.1097/iyc.0000000000000174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Brief Teacher Coaching Program for Delivering an Early Intervention Program to Preschoolers With Autism Spectrum Disorder

Abstract: There is a need for research that evaluates the effectiveness of early intervention when delivered in inclusive preschools. In this study, 3 regular preschool teachers were trained to use the Early Start Denver Model with a child with autism spectrum disorder who attended an inclusive preschool. Each teacher worked with 1 child. Teachers received eleven 60-min coaching sessions based on an adapted version of the Early Start Denver Model's parent coaching program. A multiple baseline across participants design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…For example, Education Special and Education Educational Research are also among the top ten contributing categories. Students with ASD may have educational needs that other students do not have [ 28 ], and early intervention aims to reduce the symptoms of ASD patients [ 85 ] and to improve or enhance new skills [ 85 , 86 ]. PA has shown its related benefits to ASD patients (such as stereotyped behavior and motor skills).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Education Special and Education Educational Research are also among the top ten contributing categories. Students with ASD may have educational needs that other students do not have [ 28 ], and early intervention aims to reduce the symptoms of ASD patients [ 85 ] and to improve or enhance new skills [ 85 , 86 ]. PA has shown its related benefits to ASD patients (such as stereotyped behavior and motor skills).…”
Section: Discussionmentioning
confidence: 99%
“…In the previous two decades of research, the ESDM has demonstrated implementation versatility across intervention settings and agents. Implementation of the ESDM has been effectively adapted beyond intensive university research settings (Dawson et al, 2010), to include implementation in childcare centers and preschool settings (Fulton et al, 2014; Tupou et al, 2020; Vivanti et al, 2019, 2022; Zitter et al, 2023), family homes (Holtzinger et al, 2019; Waddington et al, 2021), parent education (Mirenda et al, 2022; Rogers et al, 2021), and telehealth (Vismara et al, 2013, 2018) implementation models. Moreover, the ESDM has been implemented with positive outcomes by individuals from a wide range of expertise from interdisciplinary professionals (i.e., psychologists, speech-language pathologists, and occupational therapists) to early childcare providers and parents (Baril & Humphreys, 2017; Rogers & Dawson, 2010).…”
Section: A Critical Need For Ei In Rural Communitiesmentioning
confidence: 99%
“…These interventions, if carried out early, can cause an important and significant improvement in the deficiencies of these people [ 23 ]. In addition, early intervention can enhance other types of unaffected skills [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%